2015
DOI: 10.1007/s11101-015-9417-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamoyltransferases in plant metabolism

Abstract: Hydroxycinnamoyltransferases are enzymes transferring hydroxycinnamoyl units like cinnamoyl, 4-coumaroyl, caffeoyl, feruloyl and sinapoyl moieties from an activating residue such as coenzyme A or glucose or activated as hydroxycinnamoyl ester (e.g. chlorogenate) to an acceptor molecule, most commonly to an OH or NH 2 group as ester or amide. The hydroxycinnamoyl groups play either a ''decorating'' role or are building blocks of more complex structures. Proteins catalysing hydroxycinnamoyl transfer have been kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 173 publications
(181 reference statements)
1
26
0
Order By: Relevance
“…Phenylpropanoids are a group of plant secondary metabolites derived from phenylalanine which have a wide variety of functions both as structural and signaling molecules[36]. Plant HCTL enzyme participates in phenylpropanoid biosynthesis[37]. The marked downregulation in HCTL expression, consistent with prior reports that cotton fiber thickening is negatively related to phenylpropanoid content, suggest that the HTCL associated with phenylalanine metabolic pathways might play a key role in the fiber developmental transition process.…”
supporting
confidence: 71%
“…Phenylpropanoids are a group of plant secondary metabolites derived from phenylalanine which have a wide variety of functions both as structural and signaling molecules[36]. Plant HCTL enzyme participates in phenylpropanoid biosynthesis[37]. The marked downregulation in HCTL expression, consistent with prior reports that cotton fiber thickening is negatively related to phenylpropanoid content, suggest that the HTCL associated with phenylalanine metabolic pathways might play a key role in the fiber developmental transition process.…”
supporting
confidence: 71%
“…Play various roles including response to biotic and environmental stress. 17.7 0.0009 3.1 0.01 [ 72 , 73 ] 2245 53577 GDSL (esterases/lipases) Involved in defence from pathogens and stress, plant development, morphogenesis 30.9 4.18 e-22 9.92 4.2 e-08 [ 74 , 77 ] 51706 - lipase 6.2 0.007 - - [ 76 , 77 ] 766 9217 phospholipase 11.0 1.13 e-09 2.4 0.009 [ 76 , 92 ] - 24143 esterase - - 8.9 0.0004 [ 76 , 77 ] 15968 - cc-nbs-lrr resistance-genes in plant response to pathogens 7.7 0.0006 - - [ 82 , 83 ] 64844 - glycosyltransferase catalyzes transfer of sugars from nucleotide DP to a nucleophilic glycosyl acceptor 7.7 0.0006 - - [ 78 ] 12279 69649 udp-glycosyltransferase catalyzes conversion of cycloartenol to steroidal saponins 11.1 1.01 e-14 3.5 0.0016 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of gdsl genes in plants is still poorly understood. Recently it has been subject of much attention in studies regarding for example, gene family diversity or structural and functional studies [ 75 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of caffeoyl shikimate with buffer alone, or with enzyme extracts with low CSE activity, resulted in the appearance of a new compound with lower retention time but identical UV spectrum to the initial substrate. Initially, we thought that this compound might be an additional ester of shikimate, formed either by trans‐esterification (Petersen, ) or possibly through additional activity of HCT; this latter type of reaction has recently been reported for formation of dicaffeoyl quinate (Vanholme et al ., 2013a; Moglia et al ., ). However, MS analysis indicated that the compound could not be a dicaffeoyl ester, and, because it is formed in the absence of enzyme, it is probably an adduct formed by reaction with a component in the buffer.…”
Section: Discussionmentioning
confidence: 99%